Analisis Bentuk Kesadaran Serta Kepatuhan Hukum Bagi Masyarakat Indonesia Dalam Kehidupan Bersosialisasi - Amelia, Dean Putri; Lewoleba, Kayus K (Media Hukum Indonesia (MHI), 2024)
Law plays a crucial role in the exercise of institutional powers, as its primary function is to guarantee legal certainty within society. Consequently, every individual has the right to legal protection, which implies that law encompasses both written and unwritten rules and regulations, where in a provision it certainly regulates people's lives and provides a witness for violators who try to fight the law.  In addition, in law, of course, there is a sense of awareness and legal compliance for the community in social life, of course, all forms of legal regulations must be obeyed both written and unwritten, but in building legal awareness itself is certainly not easy, not everyone has this awareness. Therefore, the government must strive for a form of public awareness and compliance with applicable law. This research is a normative legal study, which is carried out by analyzing literature or secondary data only.